1998
DOI: 10.1111/j.1572-0241.1998.219_a.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Alendronate on Gastric and Duodenal Mucosa

Abstract: Alendronate 5 and 10 mg/day for 2 wk was associated with a lower incidence of gastric erosions than aspirin. The incidence of gastric erosions in the alendronate groups did not differ significantly from the placebo group. In this study, unlike aspirin, alendronate did not induce gastric erosions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 11 publications
3
34
0
Order By: Relevance
“…For example, in one such endoscopy study, alendronate ingestion for 2 weeks was shown to induce gastric ulcer in 30 of 227 subjects (13.2%). 25 In addition to those studies, Graham et al have also shown in a randomized trial that 10 days of combined naproxen and alendronate medication had a synergistic effect on the development of gastric ulcer in healthy subjects: 8% for alendronate, 12% for naproxen, and 38% for patients on combined therapy. 28 Those data correlate with our data in the present study, where endoscopy was performed to evaluate drug-induced gastroduodenal injuries.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…For example, in one such endoscopy study, alendronate ingestion for 2 weeks was shown to induce gastric ulcer in 30 of 227 subjects (13.2%). 25 In addition to those studies, Graham et al have also shown in a randomized trial that 10 days of combined naproxen and alendronate medication had a synergistic effect on the development of gastric ulcer in healthy subjects: 8% for alendronate, 12% for naproxen, and 38% for patients on combined therapy. 28 Those data correlate with our data in the present study, where endoscopy was performed to evaluate drug-induced gastroduodenal injuries.…”
Section: Discussionmentioning
confidence: 95%
“…40,41 The possible mechanisms of bisphosphonate-induced gastric damage have been presented as associated with the ability to attenuate the surface hydrophobic phospholipid barrier of the stomach, through direct contact of the drug to the mucosa. 42 Further, the topical irritant property of NSAID on the gastrointestinal mucosa destabilizes the surface lining of phospholipids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that the rate of acute mucosal injury due to AL was comparable to that observed with NSAIDs (7). Generally these GI side effects have been attributed to high local concentrations of the drug in patients who do not follow dosing instructions properly or to an underlying esophageal or gastric disease (1,5,7). However, even when taken as directed, amino BPs have the capacity to irritate the GI mucosa (8).…”
mentioning
confidence: 96%
“…effects (1)(2)(3)(4)(5)(6). It was reported that the rate of acute mucosal injury due to AL was comparable to that observed with NSAIDs (7).…”
mentioning
confidence: 99%